MODUL BERBASIS PBL UNTUK MEMFASILITASI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS KONTEN BARISAN DAN DERET GEOMETRI - Ilyas Mulama Hartanta; Sakur; Armis (Jurnal Ilmiah Matematika Realistik, 2026)
The background of this study stems from the inadequacy of students' mathematical problem-solving competencies alongside the scarcity of instructional materials aligned with the Merdeka Curriculum. Teacher-dominated instruction deprives learners of opportunities for autonomous exploration. Accordingly, this study intends to construct a PBL-anchored instructional package covering geometric sequences and series for phase F that is both valid and practical. An R&D approach employing the 4-D framework was adopted, encompassing define, design, develop, and disseminate stages. Product trials took place at SMKN Pertanian Terpadu Pekanbaru. Three assessors rated validity as "highly valid," yielding 97.44% for the instructional package, 96.18% for student worksheets, and 96% for assessments. The limited-scale trial produced student response rates of 92.38% and teacher response rates of 90.42%, both classified as highly practical. The broad-scale trial produced student response rates of 88.98% and teacher response rates of 91.45%, both classified as highly practical. Drawing on these findings, the PBL-anchored instructional package supporting phase F learners' mathematical problem-solving competencies on geometric sequences and series content has been verified as valid and practical.